CD30-positive lymphoproliferations and mycosis fungoides originate from the same T-cell clone and share overlapping oncogenic mutations and gene fusions when occurring in the same patient. (October 2021) - Wobser, Marion; Roth, Sabine; Appenzeller, Silke; Kneitz, Hermann; Goebeler, Matthias; Geissinger, Eva; Rosenwald, Andreas; Maurus, Katja
Abstract : Introduction: The emergence of a common progenitor cell has been postulated for the association of CD30-positive lymphoproliferative disease (LPD) and mycosis fungoides (MF) within the same patient. The underlying molecular alterations are unknown. Materials and methods: We analyzed the underlying genetic alterations of 16 samples of two patients suffering both from CD30-positive LPD and MF. Skin biopsies of respective lesions were obtained over a time course of at least 5 years. We applied targeted next generation sequencing technologies with a hybrid capture-based DNA library preparation approach to detect mutations. For the identification of fusion transcripts we took advantage of an anchored multiplex PCR next generation sequencing assay. Results: Oncogenic fusions affecting the JAK/STAT signaling pathway were present in all samples obtained both of lesions of CD30-positive LPD and MF. We identified a NPM1-TYK2 fusion in patient 1 and an ILF3-JAK2 fusion in patient 2. In one patient, only the lesions of histologically proven CD30-positive LPD exhibited additional STAT5A mutations that were not present in the MF lesions. Conclusion: CD30-positive LPD and MF show overlapping molecular profiles when occurring within the same patients. Our data imply that constitutive activation of the JAK/STAT signaling pathway by means of mutations and fusions may play a central role for the molecular pathogenesis of both entities.